Forekomsten av angst- og depresjonssymptomer hos samiske og ikke-samiske elever i videregående skole i Finnmark i 1994 og 2014 - Siv Kvernmo; Ronja Sæterhaug Bye (Norsk Forening for Epidemiologi, 2019)
Kvernmo S, Bye RS. The prevalence of anxiety- and depression symptoms in Sami and non-Sami high school students in Finnmark county in 1994 and 2014. Nor J Epidemiol 2019; 28 (1-2): 15-25. ENGLISH SUMMARY As much as 15-20% of children and adolescents in Norway, aged 3-18 years, are suffering from anxiety, depressive or behavioral problems. Recent studies have shown an increase in the prevalence of emotional problems among adolescents during the last decades. The aim of this study is to examine the prevalence and the sociodemographic and psychosocial predictors of anxiety and depression symptoms in Indigenous Sami and non-Sami adolescents in 1994 to 2014. Data from 1655 high school students in the Young in North (Ung i Nord) study from 1994 was compared to data from 1856 high school students in Ungdata, conducted in 2014 in the same area. Similar and comparable measures were applied in the two studies with SCL-12 as the main measure. The results showed an increase in the prevalence of depression and anxiety symptoms from 1994 compared to 2014, but a decrease in behavioral problems. At both years females reported more problems. No significant ethnic differences occurred in rates of problems between indigenous Sami and non-Sami adolescents at any time point. Across gender and ethnic groups, self-esteem and the students' relationship to the school were the two strongest predictors. Conclusion: This study confirmed findings from other studies of an increase of rates of anxiety and depression symptoms in older adolescents over the last decades, but also in types of significant predictors. Our findings entail a future need for prevention and treatment offers to adolescents suffering from anxiety and depression problems.